Program Directors’ Opinions About Otolaryngology Resident Teaching Medical School Anatomy - Wanstreet, Tyler (Cureus, 2020)
Purpose To evaluate whether otolaryngology residency program directors (PDs) provide residents to teach pre-clinical medical students anatomy and to outline their perceptions of this practice. Methods An anonymous online survey was sent to active U.S. otolaryngology residency PDs in 2019, assessing each program’s involvement in teaching medical student anatomy. Results Forty-five of 121 (37.1%) of surveyed otolaryngology PDs responded. Sixteen of the 44 (36.4%) residency programs that were associated with a medical school provided residents to teach anatomy (“Teaching Programs”). The 29 (64.4%) remaining programs did not provide residents (“Non-teaching Programs”). No significant differences were found between Teaching and Non-teaching Programs (P<0.05) for the size of the program, the presence of fellowships, the size of medical school, whether residents had won teaching awards, or the number of otolaryngology residency applicants from that school. In general, all PDs responded positively about residents teaching medical school anatomy. Non-teaching Programs primarily cited not being approached by the medical school as a reason for not providing residents to teach. Conclusion The majority of respondent otolaryngology PDs have a positive view of residents teaching medical students but few do it. Otolaryngology departments will need to take the lead on developing opportunities to put students and residents together for anatomy education.